Simulasi Pemadam Kebakaran Otomatis Menggunakan Sensor Api Berbasis Arduino Uno - Asni Tafrikhatin; Rouf Wangafif; Jati Sumarah; Ajeng Tiara Wulandari; Apriansyah Zulatama (Politeknik Piksi Ganesha Indonesia, 2023)
One of the efforts to prevent fires is by providing occupational health and safety (K3) learning. In the learning process, the material is only in videos and power points about fire prevention and control. Conversely, students more easily understand contextualized material. One of them is an automatic fire extinguisher simulation. This simulation uses a fire sensor as its input, Arduino uno as its control, and a relay as an output from Arduino. This learning media was tested on 40 people with backgrounds as students and employees. Based on the results of this learning media trial, the average questionnaire assessment reached 87.6%, so this learning medium is effective as a learning medium for fire extinguisher simulation.